Potensi Sari Pati Daun dan Bunga Kecombrang (Etlingera hemisphaerica) dalam Menghambat Pertumbuhan Bakteri Salmonella typhi - Kusmiati, Iis; Nopiyanti, Nopa; Arisandi, Destien Atmi (Jurnal Biosilampari : Jurnal Biologi, 2025)
This study aims to determine the potential of Etlingera hemisphaerica leaf and flower extracts against the inhibition zone of Salmonella typhi. The study was conducted experimentally using a post-test only control group design. Torch ginger leaf and flower extracts were prepared with varying doses of 70 grams, 80 grams, 90 grams, and 100 grams, with chloramphenicol as a positive control. Antibacterial tests were conducted using disc diffusion method paper on Nutrient agar media, and the diameter of the inhibition zone was measured using a caliper. Data analysis was performed using the non-parametric Kruskal–Wallis test because the data were not normally distributed and not homogeneous, and continued with the Mann–Whitney test. The results of the Kruskal–Wallis test showed an Asymp.Sig value of 0.000 <0.05, which means there were significant differences between treatments. Doses of 90 grams and 100 grams produced moderate inhibition and indicated antibacterial effectiveness. This shows that the essence of Etlingera hemisphaerica leaves and flowers is effective in inhibiting the growth of Salmonella typhi and can be used as an alternative based on local wisdom.